Traditional, cyberbullying, and suicidal behaviors in Argentinian adolescents: the protective role of school, parental, and peer connectedness - Dadras, Omid; Takashi, Naoki (Frontiers in Psychiatry, 2024)
Introduction Bullying, both in person and online, is a significant risk factor for a range of negative outcomes including suicidal behaviors among adolescents and it is crucial to explore the protective effects of parental, school, and peer connectedness on suicidal behaviors among victims. Methods This study is a secondary analysis of the Argentina Global School-based Student Health Survey (GSHS 2018). Logistic regression analysis, adjusting for age and sex, determines the likelihood of suicidal thoughts and attempts among bullying victims. To explore the modifying effect of school, parental, and peer connectedness on the association between bullying and suicide behaviors, the interaction term was included. Sampling design and weights were applied in all analyses in STATA 17. Results The study included 56,783 students in grades 8-12, with over half being female. Adolescents aged 14-15 exhibited the highest prevalence of bullying, cyberbullying, suicidal thoughts, and attempts, with females displaying a higher prevalence in all measured categories. The study found that adolescents who reported being bullied or cyberbullied demonstrated a significantly higher likelihood of experiencing suicidal thoughts and attempting suicide. Furthermore, protective factors such as school, parental, and peer connectedness were found to play a critical role in mitigating the adverse impacts of bullying and cyberbullying on suicidal thoughts and attempts. Conclusion The findings underscore the critical prevalence of both bullying and cyberbullying among school-going Argentinian adolescents and their profound association with suicidal behaviors. The study emphasizes the importance of supportive family environments and peer and school connectedness in mitigating the negative effects of bullying and cyberbullying on mental health and suicide risk among adolescents.